Nota sulla sentenza nel processo di appello - Pavanello, Pierantonio (Quaderni di diritto ecclesiale, 2014)
This short note presents the peculiar properties of a sentence in an appeal process. Such sentence does not have as ist object the sentence given at the previous jugdement, but the moral certainty concerning the nullity/validity of the marriage. That which is confirmed (or reformed) is, in fact, the dispositive part of the sentence. In the in iure section there should be presented those specific principles to which it was resorted for a solution of the case and in the in facto section there should be examined together both the elements of proof that would have been gathered in the previous degree of judgement and those resulting from the ordinary examination of the sentence, placing them within the core of a coherent frame.